(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the gingival status among dental students (first-year students and third-year students) in Ha Noi Medical University. Method: A cross-sectional study using the gingival index (GI). Result: The prevalence of gingivitis was 90,4% (first-year student 86,96%, third-year students 94,64%). Conclusion: The prevalence of gingivitis was high. Properly designed oral health educational programs should be implemented to improve their knowledge and behavior toward oral health.